Assessment of business trust level in Vladivostok state university of economics and service - Varkulevich, Tatyana V.; Pashuk, Natalya R. (Nexo Revista Científica, 2022)
The main purpose of this article is to assess the level of trust in the Vladivostok State University of Economics and Service (after this referred to as VSUES) among business structures. To achieve this goal, the following research methods were used: information and comparative analysis, content analysis, survey method, expert assessments, rating, hierarchy analysis method, and index method. The information base of the research was made up of the mission and development strategy of the university, the analytical materials based on the monitoring results of the university effectiveness in 2016-2019, statistical and analytical information posted on federal and regional portals. After the step-by-step assessment, it was revealed which trust criteria of VSUES are insufficient and satisfactory. Based on the analysis of the calculation results, the proposals were formulated that contribute to entrepreneurs' trust level increase in the university.